Redox conditions of bottom sediments and macrozoobenthos characteristics in the Kruglaya and Kazachya bays (Sevastopol) - N. A. Orekhova (A. O. Kovalevsky Institute of Biology of the Southern Seas of RAS, 2021)
A lack of systemic and environmentally efficient approach to exploitation of the Kruglaya and Kazachya bays (Sevastopol) resulted in their severe pollution. The conjunction of natural and anthropogenic factors led to deterioration of habitat conditions of benthic communities. The aim of this work was to carry out complex research of Kruglaya and Kazachya bays’ ecosystems to study peculiarities of formation of redox conditions in bottom sediments and bottom water layer, as well as their effect on macrozoobenthos characteristics. Bottom sediments were sampled by diver in plexiglass tubes hermetically sealed at the top and bottom; it helped in preserving a fine structure of bottom sediments and bottom water layer. To study benthic communities, samples were taken in the same spot with a manual sampler. To obtain chemical composition of pore waters with high vertical resolution, the voltammetry analysis was carried out. Calculation of an oxygen flux at the boundary and in the upper layer of bottom sediments was performed according to the vertical profile of oxygen concentration in pore waters and geochemical analysis with applying the equation for the Fick’s first law and considering concentration gradient and molecular diffusion of oxygen in pore waters. Standard hydrobiological methods were applied for the analysis of benthic material. When calculating the values of the Shannon diversity index (H’), the binary logarithm was used. The data analysis showed as follows: a high level of anthropogenic load and restricted water dynamics resulted in siltation of bottom sediments in the studied water areas, which obstructed oxygen penetration; the accumulation of organic carbon contributed to its active consumption. Stratification of a water column due to limited water exchange, high temperature of bottom water, accompanied by a decrease in oxygen solubility, and finely dispersed nature of bottom sediments contributed to the fact that the rate of oxygen input was lower than the rate of oxygen consumption for organic matter oxidation. This was followed by the development of oxygen deficiency zones and emergence of reduced compounds, in particular hydrogen sulfide. Importantly, suboxic conditions prevailed in the upper sediment layer, and anaerobic conditions prevailed below. Due to this, the main forms of macrozoobenthos were species tolerant to oxygen deficiency and organic pollution. Specifically, in some spots of the Kazachya Bay, polychaetes alone were recorded. At the same time, in the Kruglaya Bay mouth area, intense water dynamics and morphological peculiarities of bottom sediments contribute to saturation of the upper sediment layer with oxygen. Based on oxygen concentration data for the surface (0–5 mm) sediment layer (pore waters) and on geochemical peculiarities of bottom sediments (moisture and porosity), the oxygen flux at st. 4 (the Solenaya Bay) was calculated; the value was 0.73 M·m−2·year−1. Considering oxygen concentration in bottom water layer (259 μM), the time for complete depletion of oxygen or its renewal is about 5 months if taking into account biogeochemical processes alone. Hence, it can be assumed that the ecosystems of the Kruglaya and Kazachya bays are in the stage of degradation. Their further exploitation without a developed systemic and rational approach will result in a critical deterioration of the ecosystems – the emergence and spread of environmental risk zones. It will reduce the recreational and socioeconomic attractiveness of these areas.